2021
DOI: 10.1021/acs.energyfuels.1c00620
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Dual Polymers and Sand-to-Fines Ratio for Enhanced Flocculation of Oil Sand Mature Fine Tailings

Abstract: The current challenges in dewatering oil sand mature fine tailings (MFTs) by flocculation using a single flocculant include the requirement of very high doses and high cost, inefficient flocculation, and low content of solids in sediment. The obtained flocculated sediment with less than <40 wt % solids is difficult in further consolidation and dewatering for the final disposal. In this work, we examined a new approach for dewatering by dual polymer flocculation in combination with varying sand-to-fines ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The 1 H NMR spectra of AETAC-co-AAm with 14% and 23% AETAC in D 2 O (1% w/v) showed a higher multiplicity than the corresponding spectra of AETAC-co-AAm with 42% and 54% AETAC, and a stiff rod-like structure of the copolymer chains at higher AETAC compositions was suggested. This interpretation was consistent with the 13 C NMR spectra of AETAC-co-AAm, in which the number of resonances with higher AETAC compositions was smaller than that with lower AETAC compositions [6].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The 1 H NMR spectra of AETAC-co-AAm with 14% and 23% AETAC in D 2 O (1% w/v) showed a higher multiplicity than the corresponding spectra of AETAC-co-AAm with 42% and 54% AETAC, and a stiff rod-like structure of the copolymer chains at higher AETAC compositions was suggested. This interpretation was consistent with the 13 C NMR spectra of AETAC-co-AAm, in which the number of resonances with higher AETAC compositions was smaller than that with lower AETAC compositions [6].…”
Section: Introductionsupporting
confidence: 87%
“…Because it comprises polyelectrolytes, AETAC-co-AAm provides better flocculation than nonionic polyacrylamide (PAAm) [7][8][9][10]. In recent years, more than two kinds of acrylamide-based polymer flocculants have been used because sludge dewatering has become difficult owing to increasing organic matter content in wastewater [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why zeta potential modifiers reduce permeability by <1% and have a high penetration depth. Zeta potential modifiers are generally cationic and require negatively charged formations such as sandstones, so they are not applicable in positively charged carbonate formations. , This method can be used in formations with a permeability of several millidarcies to several darcies with low risk. For this purpose, modeling can be used to find operational parameters such as type of injection, pressure, and injection rate. , …”
Section: Chemical Treatment For Sand Controlmentioning
confidence: 99%
“…[ 16 ] Recently, Zhou et al combined anionic PAM with a hybrid aluminium hydroxide‐PAM to treat MFT slurries with different sands‐to‐fine solids ratios. [ 14 ] They found that the dual polymer system needed lower doses and that sediments with higher solids contents could be produced with the addition of larger sand particles. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%